PENGELOLAAN KEUANGAN DAN PENERAPAN PENGENDALIAN INTERNAL PADA KEGIATAN ISRA MI’RAJ DI MASJID BAITURRAHMAN - Raliya Putera, Idrisi; Nurdin, Nurdin; Rachman, Afandi; Wicaksono, Adi; Sutrisno, Hadi; Hajarudin, Hajarudin (Jurnal Pengabdian Kepada Masyarakat, 2025)
The Baiturrahman Mosque is a PKM partner that facilitates the Isra Mi'raj which has been carried out for approximately 25 years. In this PKM activity, the team brought up a big topic, namely Building a Generation with Noble Morals: STIE Ganesha Social Service in Commemoration of the Isra Mi'raj of the Prophet Muhammad SAW. To support this topic, researchers evaluated the implementation of internal control of funds for Isra Mi'raj activities at the Baiturrahman Mosque using a qualitative descriptive implementation method.  In carrying out the evaluation, researchers collected data by means of observation and interviews. Primary data in the form of internal control of the receipt of funds for Isra Mi'raj activities was obtained through questions and answers with Mr. Ajat, Mr. Sugeng, and Mr. Sarkum as chairman and members of the Baiturrahman Mosque committee. Based on the data collected, researchers found that the implementation of internal control in the implementation of Isra Mi'raj activities at the Baiturrahman Mosque in 2024 still needs to be optimized.